Struktur Modal, Ukuran Perusahaan, Likuiditas dan Profitabilitas Perusahaan Manufaktur yang Listing di BEI - Susiyanti Susiyanti; Bahtiar Effendi (Owner : Riset dan Jurnal Akuntansi, 2019)
This study aims to determine the effect of capital structure, firm size and liquidity on profitability in manufacturing companies food and beverage sub-sector listed on the stock exchange Indonesia. This study uses a quantitative approach. Data collection techniques used in this study is the method of documentation that is by collecting and recording financial statements. Sources of data used are secondary data in the form of financial statements of food and beverage manufacturing companies listed on the BEI period 2014-2016 which can be obtained through the website www.idx.co.id. The sampling technique used is purposive sampling with the number of respondents 13 companies. The method of data analysis used is multiple regression linear regression analysis using SPSS 24.0 program aid. The result of research indicates that (1) partially capital structure has a significant negative effect on profitability, (2) firm size has significant positive effect on profitability, (3) liquidity has significant negative effect on profitability, (4) simultaneously capital structure, firm size, and liquidity has a significant influence on the profitability of manufacturing companies food and beverage sub-sector listed in Indonesia stock exchange.